2018
DOI: 10.3892/ol.2018.8819
|View full text |Cite
|
Sign up to set email alerts
|

Role of the SOX18 protein in neoplastic processes (Review)

Abstract: Abstract. There is a high demand for anticancer drugs due to the fact that the chemotherapeutics currently used have numerous side effects, which lowers the patient's quality of life. However, the latest antibody therapies are extremely expensive, hence the requirement to identify novel, equally effective but low-toxic treatments that have limited side effects. As a result of this, a number of research centres around the world are attempting to identify novel molecular markers that could be effective targets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Although SOX18 is involved in a variety of patho-physiological processes (Olbromski et al, 2018), HLTRS is a rare and severe vascular disorder. In order to further investigate propranolol in this disease scenario, we used a mouse model of HLTRS, SOX18 Ragged Opossum ( RaOp ) (Pennisi et al, 2000; Slee, 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Although SOX18 is involved in a variety of patho-physiological processes (Olbromski et al, 2018), HLTRS is a rare and severe vascular disorder. In order to further investigate propranolol in this disease scenario, we used a mouse model of HLTRS, SOX18 Ragged Opossum ( RaOp ) (Pennisi et al, 2000; Slee, 1957).…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that expression of SOX18 transcription factor is increased in numerous cancer types, for example, gastric stromal tumors, pancreatic, liver, ovary, and breast cancer, 7‐10 it seems that this transcription factor may play a fundamental role in the processes of cancer promotion and progression.…”
Section: Discussionmentioning
confidence: 99%
“…SOX18 belongs to group F and is involved in maturation and differentiation of endothelial cells prenatally and in angiogenesis 5 and lymphangiogenesis postnatally 6 . Recent studies detected upregulation of SOX18 in various kinds of human neoplasm and suggested that it may have an oncogenic role in tumor promotion and progression 7‐10 . However, its contribution in NMSCs is not yet elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time that SOX18 is associated to a key function in viral life cycle. It has so far been linked to the transcriptional regulation of ECs and to the progression of solid cancers 34, 35 . SOX18 forms a dimer 20, 21 , able to bind to the viral and cellular genomes.…”
Section: Discussionmentioning
confidence: 99%